2014
DOI: 10.1056/nejmoa1314981
|View full text |Cite|
|
Sign up to set email alerts
|

Spread of Artemisinin Resistance in Plasmodium falciparum Malaria

Abstract: BACKGROUND Artemisinin resistance in Plasmodium falciparum has emerged in Southeast Asia and now poses a threat to the control and elimination of malaria. Mapping the geographic extent of resistance is essential for planning containment and elimination strategies. METHODS Between May 2011 and April 2013, we enrolled 1241 adults and children with acute, uncomplicated falciparum malaria in an open-label trial at 15 sites in 10 countries (7 in Asia and 3 in Africa). Patients received artesunate, administered or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

60
1,981
8
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,880 publications
(2,095 citation statements)
references
References 32 publications
60
1,981
8
12
Order By: Relevance
“…The emergence and re‐emergence of infections caused by HIV, Ebola virus and Zika virus has put great pressure on the development of vaccines and new specific therapeutics. The rapid appearances of drug‐resistant pathogens such as drug‐resistant bacteria, fungi, parasites and viruses have been widely reported (Snitkin et al , 2012; Ashley et al , 2014; McCarthy, 2016; Takeda et al , 2017). …”
Section: Introductionmentioning
confidence: 99%
“…The emergence and re‐emergence of infections caused by HIV, Ebola virus and Zika virus has put great pressure on the development of vaccines and new specific therapeutics. The rapid appearances of drug‐resistant pathogens such as drug‐resistant bacteria, fungi, parasites and viruses have been widely reported (Snitkin et al , 2012; Ashley et al , 2014; McCarthy, 2016; Takeda et al , 2017). …”
Section: Introductionmentioning
confidence: 99%
“…The possibility of these parasites spreading to Africa – a potential public health disaster – has prompted a shift from malaria control to elimination in South East Asia [1–4]. As part of a package of interventions, referred to as Targeted Malaria Elimination (TME), mass antimalarial administration – the presumptive treatment of an entire community to interrupt completely local malaria transmission – is currently under study across the region [5].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the latter study demonstrated that slow parasite clearance was observed in malaria patients from western Cambodia irrespective of whether they had been treated with monotherapy, or with artemisinin-based combination therapy (ACT), but this was not observed in patients from the Thailand-Myanmar border to the northwest. Extensive multicentre studies led by the UK-funded TRAC consortium then provided important evidence, just a few years later, that the slow-clearance phenotype was spreading through P. falciparum populations in the Greater Mekong subregion (GMS) in association with certain variants of the pfk13 gene, but that in parallel African studies any treatment failures seen were not associated with this genetic marker [3].…”
Section: A New Artemisinin Susceptibility Phenotype Arises In Asiamentioning
confidence: 99%
“…Alone among these few loci, mutations in pfk13 were also found to correlate with ex vivo DHA susceptibility of Cambodian parasites in the RSA, although the exact mutation identified in mutant F32 parasites has still not been encountered in any wild P. falciparum isolates to date [9]. The identification of key variants of pfk13 that correlate both with slow clearance in patients receiving artesunate monotherapy [3] and with ex vivo RSA data [6] has enabled subsequent research on pfk13. This includes:…”
Section: A New Artemisinin Susceptibility Phenotype Arises In Asiamentioning
confidence: 99%
See 1 more Smart Citation